2016
DOI: 10.3390/ijerph13111119
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution in Settled Dust Associated with Different Urban Functional Areas in a Heavily Air-Polluted City in North China

Abstract: Understanding variations of heavy metals in atmospheric particles between different functional areas is significant for pollution control and urban planning in cities. To reveal pollution and spatial distribution of heavy metals in atmospheric particles from different urban functional areas in Shijiazhuang in North China, 43 settled dust samples were collected over the main urban area and heavy metal concentrations were determined in their <63 µm fractions using an ICP-OES. The results suggest that Cr, Mn, Fe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The high concentrations of Cl − and Na + likely originate from dry lake deposits (Abuduwaili et al, 2015), which are spread over the northern area of Beijing. Elevated heavy metals suggest the presence of fugitive dust mixed with industry or traffic emissions (Wan et al, 2016). The high loadings of NO − 3 and NH + 4 in Factor 2 indicate traffic emissions .…”
Section: Source Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The high concentrations of Cl − and Na + likely originate from dry lake deposits (Abuduwaili et al, 2015), which are spread over the northern area of Beijing. Elevated heavy metals suggest the presence of fugitive dust mixed with industry or traffic emissions (Wan et al, 2016). The high loadings of NO − 3 and NH + 4 in Factor 2 indicate traffic emissions .…”
Section: Source Profilesmentioning
confidence: 99%
“…With the increasing PM 2.5 concentration in northern China, winter haze occurrences increased from 3 to 16 days per year during 2000-2012 (Wang and Chen, 2016). The frequency of haze events during winter is enhanced by meteorological conditions; the minimum daily temperatures typically reach −15 to −20 • C (Wu et al, 2012) and the boundary layer height becomes shallow, to less than 100 m .…”
Section: Introductionmentioning
confidence: 99%
“…In soil, mercury is most commonly encountered in organic (Hg -C ) and inorganic (Hg 2+ ) forms (Lymberidi 2005;UNEP 2013), the presence of which affects the soil quality characteristics including natural soil profile and soil fertility values (Laker 2005). Since recent years the mercury contamination issue has become increasingly topical in regard to urban soils (Li et al 2010;Szymon Różański 2015;Gray et al 2015;Wan et al 2016;Kumar et al 2017;Moller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our study area is located in an industrialized region, Yangtze River Delta and surrounded by several large cities, including Shanghai, Suzhou, and Nanjing [67,70]. Moreover, during autumn and winter, the strong monsoon can carry the pollution from Northern China, and several recent studies indicated the linkage between industry and heavy metal pollution in water [50,60]. By consulting similar areas, the concentrations of Hg and Pb are close to those in Lita Watershed [61].…”
Section: Source Identification Of Aquatic Heavy Metals and Nutrientsmentioning
confidence: 74%